Can public service motivation increase work engagement?—A meta-analysis across cultures - Ding, Mengxiao; Wang, Chengli (Frontiers in Psychology, 2023)
Civil servants' work engagement is an essential topic in human resource management research of public sector. To explore the effects of public service motivation on civil service engagement as well as its mechanisms of action, and boundary conditions, this paper utilizes a meta-analytic approach to analyze 31 independent samples from 10 countries through literature search, screening, and coding. The result shows a significant positive relationship between public service motivation and work engagement with no possibility of publication bias. The regulatory effect test through Hofstede's model reveals that the dimensions of Power Distance Index, Individualism/Collectivism, Long-Term Orientation/Short-Term Orientation, and Indulgence/Restraint can significantly moderate the relationship between public service motivation and work engagement. This study provides a clear explanation for understanding the relationship between public service motivation and work engagement from a cross-cultural perspective, meanwhile it offers some theoretical implications for improving public servants' work engagement in the future.